INTEGRAL AND QUALIFIED CRIMINAL LAW ENFORCEMENT MODEL IN DEALING WITH VEHICLE ROBBERY: A LEGAL STRENGHTENING - Heni Siswanto; Maroni Maroni; Fathoni Fathoni (Muhammadiyah Law Review Journal, 2017)
The crime of theft with violence, theft of motorcycles, and robbery have spread terror massively. It becomes a very frighteningly specter for people in Lampung. To resolve it, it is necessary to build a "Criminal Law Enforcement Policy" (CLE) through effective policy. The question of this paper are about the condition of the existing model of CLE against the crimes in Lampung; and the application of integral and quality of the CLE model of in dealing with crime and robbery on the investigation in the future. The research approach used is legal study (jurisprudence) approach, which is based on ideas and the recent approach. The first step of this research begins with doctrinal legal research by using statute approach, an analytical approach (analytical approach), and the conceptual approach. As a complement, it also uses the approach of socio-legal studies, which examine the law as a social phenomenon related to the enforcement of criminal law. The research location in the jurisdiction of the Lampung Police. The final results are expected to be obtained through legal research are building a model of the integral and qualified CLE applications in dealing with the crime of vehicle theft on the stage of investigation. Model application of CLE will be able to provide guidance in combating this crime, effective, non-transactional, and based on the science of law. The most relevant application model was applied in accordance with the typology and characteristics of the Lampung Police jurisdiction.